Internacionalização dos programas de pós-graduação stricto sensu: o caso da Universidade Federal da Paraíba - Lima, Rubem Alves de (2019)
The internationalization of higher education has been an element of distinction for excellence graduate programs (PPGs). Actions such as international cooperation agreements and projects and the increase in the number of publications in international co-authorship have been strategies to raise the rating of PPGs in the evaluations carried out by the Coordination of Improvement of Higher-Level Personnel (Capes). This research aimed to analyze the internationalization process of stricto sensu graduate programs at the Federal University of Paraíba (UFPB). Its theoretical framework is based on discussions about internationalization of higher education and its relations with globalization. Thus, the work of researchers with expressive performance on the issue such as Bonaventura de Sousa Santos, Jane Knight, Hans De Wit, Marília Costa Morosini, Alda Araújo Castro, Luciane Stallivieri, among others, were used. The research is a case study using a qualitative approach and a descriptive and exploratory nature. The data collection was performed through documentar research and semi-structured interviews with the coordinators of stricto sensu graduate programs at UFPB, campus I, located in João Pessoa, Paraiba. For the data, the Content Analysis Technique proposed by Laurence Bardin (2011) was used, which follows three fundamental steps: pre-analysis, material exploration and the results treatment (inference and interpretation). Based on the analysis, a SWOT Matrix was elaborated, which presents negative and positive aspects in the internationalization process developed by the UFPB graduate programs. The analysis indicated the deficiency in foreign language by students and some teachers, administrative bureaucracy, inadequate infrastructure, resource contingencies by the MEC, among others, as negative aspects. The positive aspects were, mainly, the support to the PPGs by the Office of the Dean for Graduate Education and by the Office of the Dean for Research, the recruitment of visiting professors, the academic mobility programs, the UFPB approval in the Capes Institutional Internationalization Program (PrInt), the creation of the UFPB International Cooperation Agency and the updating of internal resolutions. Finally, actions were proposed to improve this process developed by the PPGs of this institution, such as establishing a Permanent Internationalization Commission and creating the Institutional Register of Internationalization Actions.